The Effect of Village Fund Management on Development in Foikhugaga Village, Umbunasi District, South Nias Regency - Dewi, Ratna Sari; Zai, Romi Kurniawan; Melati, Addriani Sukma (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to examine the effect of village fund management on village development in Foikhugaga Village, Umbunasi District, South Nias Regency. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 57 respondents consisting of village officials and community members of Foikhugaga Village. The data analysis techniques used were Product Moment correlation, coefficient of determination, and t-test. The results showed that village fund management was in the high category with an average value of 4.20, while village development was also in the high category with an average value of 4.21. The correlation analysis indicated a coefficient value of 0.39, which means that the effect of village fund management on village development falls into the low category. The magnitude of the effect of village fund management on village development was 15.21%, while the remaining percentage was influenced by other factors outside this study. Nevertheless, the t-test results showed that village fund management had a positive and significant effect on village development. Therefore, improving the professionalism of village officials and strengthening supervision are necessary to optimize village fund management in supporting village development.